Millennial- to centennial-scale climate periodicities and forcing mechanisms in the westernmost Mediterranean for the past 20, 000 yr. Issue 1 (January 2014) - Rodrigo-Gámiz, Marta; Martínez-Ruiz, Francisca; Rodríguez-Tovar, Francisco J.; Jiménez-Espejo, Francisco J.; Pardo-Igúzquiza, Eulogio
Abstract: Cyclostratigraphic analysis conducted on a continuous high-resolution marine record from the western most Mediterranean reveals well-identified paleoclimate cycles for the last 20, 000 yr. The detrital proxies used (Si/Al, Ti/Al, Zr/Al, Mg/Al, K/Al, Rb/Al) are related to different sediment-transport mechanisms, including eolian dust and fluvial runoff, which involve fluctuations in the atmosphere–hydrosphere systems. These fluctuations are accompanied by changes in marine productivity (supported by Ba/Al) and bottom-water redox conditions (Cu/Al, V/Al, Zn/Al, Fe/Al, Mn/Al, U/Th). Spectral analysis conducted using the Lomb–Scargle periodogram and the achieved significance level implemented with the permutation test allowed us to establish major periodicities at 1300, 1515, 2000, and 5000 yr, and secondary peaks at 650, 1087, and 3000 yr. Some of these cycles also agree with those previously described in the North Atlantic Ocean and circum-Mediterranean records. The periodicities obtained at 2000 and 5000 yr support a global connection with records distributed at high, mid, and low latitudes associated with solar activity, monsoonal regime and orbital forcing. The 1300- and 1515-yr cycles appear to be linked with North Atlantic climate variability and the African monsoon system. Thus, the analyzed record provides evidence of climate cycles and plausible forcing mechanisms coupled with ocean–atmosphere fluctuations.